STUDY OF FINANCIAL LITERACY MEASUREMENT INDICATORS FOR INDEPENDENT COFFEE SHOP MSMES; A LITERATURE REVIEW - Sudono, Agus (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2023)
This study aims to find a synthesis of journal publications related to standard indicators for measuring financial literacy in MSMEs that can be adapted to measure financial literacy in independent coffee shops. The research method used is a systematic literature review (SLR). The databases used are Google Scholar, Emerald, SAGE, and Taylor and Francis. The results showed that the measurements were carried out using item response theory (IRT), interviews, and secondary data studies. Aspec that is measured includes knowledge, awareness, attitudes, behaviors, skills, performance, investment instruments, and general information related to the macroeconomy. The researcher recommends conducting research to measure the level of financial literacy in independent coffee shops in Indonesia. Keywords: financial literacy, SLR, indicators, independent coffee shop ABSTRAK Penelitian ini bertujuan untuk menemukan sintesis dari publikasi-publikasi jurnal terkait standar indikator pengukuran literasi keuangan pada UMKM yang dapat diadaptasi untuk mengukur literasi keuangan pada kedai kopi independen. Metode penelitian yang digunakan adalah systematic literature review (SLR). Database yang digunakan adalah Google Scholar, Emerald, SAGE, dan Taylor and Francis. Hasil penelitian menunjukan pengukuran dilakukan menggunakan item response theory (IRT), wawancara, dan studi data sekunder. Aspek yang diukur meliputi pengetahuan, kepedulian, sikap, perilaku, keahlian, kinerja, instrumen investasi, dan informasi umum terkait ekonomi makro. Peneliti merekomendasikan untuk dilakukan penelitian untuk mengukur level literasi keuangan pada kedai kopi independen di Indonesia. Kata kunci: literasi keuangan, SLR, indikator, kedai kopi independen